Micronutrient Substitution of Huett’s Lettuce Formulation on Lettuce (Lactuca sativa L.) Growth in Two Static Hydroponic Systems - Putri, Nanda Cardilla; Nyayu, Nyayu Siti Khodijah; Saputra, Herry Marta (Jurnal Hortikultura Indonesia, 2022)
Lettuce is a horticultural crop that has high economic value. Lettuce plants are widely cultivated with a hydroponic system. Efforts to increase the growth and production of lettuce can be done by providing nutrients and using the right hydroponic system. This study aimed to determine the effect of micronutrient modification on the Huett’s Lettuce formulation and static hydroponic system on the growth and yield of lettuce and their interactions. The method used in this research is Randomized Complete Factorial Design (RCFD) with 3 replications. The first factor is a static hydroponic system which consists of 2 levels of treatment, namely the wick system (S1) and the kratky system (S2). The second factor is Huett’s Lettuce formulation which consists of 5 levels, namely Huett’s Lettuce formulation (H0), Huett’s Lettuce macro formulation + 20 g micro-nutrient complex (H1), Huett’s Lettuce macro formulation + 30 g micro-nutrient complex (H2), Huett’s Lettuce macro formulation + 40 g micro-nutrient complex (H3), Huett’s Lettuce macro formulation + 50 g micro-nutrient complex (H4). The results showed that the hydroponic system and modification of the Huett’s Lettuce formulation had a significant effect on the growth and production of lettuce. Kratky system (S2) provides the best results for the growth and production of lettuce. The formulation of Huett’s Lettuce macro + 20 g micro-nutrient complex (H1) provides the best results for the growth and production of lettuce plants. There was no interaction between the two treatment factors.Keywords: kratky system, micro-nutrient complex, wick system